INTER AKSI AGAMA DAN BUDAYA - Yuli Darwati, Mohammad Arif dan (IAIN Kediri, 2018)
This paper will try to explain the relationship between religion and culture. These two topics are the most important items that are inseparable in the history of human civilization from the classical to the modern period. Religion is ahuman belief system that is related to God. If the rule comes from God, then it cannot be said to be a culture, because it is not human creation, but God’s creation that is absolute. Religion is interpreted as part of the life (culture) ofindividuals or groups, each of which has the authority to understand religion and apply it. With the characteristics as indicated by Fazlur Rahman, wherever religion is located, it is hoped that it can provide guidance on values or moralsfor all activities of human life, whether social, cultural, economic or political. Not infrequently also religion becomes a determining factor in the adhesive process of social cultural interaction of the community as well as unifying thenation. Culture and religion are something different but can influence each other so that new cultures or mixing of cultures emerge. The opinion of Endang Saifudin Anshari who said in his writing that religion and culture do notinclude each other, in principle one is not part of the other and each consists of itself. Between them, of course, they are closely related like us, we see in everyday life and human life. As also seen in the close relationship between husband and wife who can give birth to a son but the husband is not part of the wife, and vice versa. Religion and culture are two different things but cannot be separated. The existence of a religion will be greatly influenced and affect thepractice of a religion in question. And conversely, a culture will be greatly influenced by the beliefs of the society in which culture develops. Therefore religion is not only an individual problem but religion is also a social affair whichultimately religious people are not only able to give birth to individual piety but also must be able to give birth to social piety.Key words: Interaction, Religion, Culture,